(untitled) (Aporte Santiaguino, 2024)
The objective of the research work was to obtain empirical equations for estimating the intensities of maximum annual rainfall of different durations and return periods in the city of Huaraz, which serve for the hydrological design of hydraulic storm drainage structures. The maximum annual rainfall in 24 hours from the Santiago Antúnez de Mayolo meteorological station best fits the Gumbel probability distribution, for this purpose the MINITAB 20 software was used. With the Dyck – Peschke equation, the maximum annual rainfall was disaggregated for durations of less than 24 hours. With these disaggregated values, the empirical equations of the intensities of maximum annual rainfall of different durations at the Santiago Antúnez de Mayolo meteorological station were obtained. The Koutsoyannis equation is the most appropriate for precipitation intensities for durations less than 24 hours and different return periods for the Santiago Antúnez de Mayolo – Huaraz meteorological station.